Sex in Penicillium series Roqueforti - J. Houbraken; J.C. Frisvad; R.A. Samson (IMA Fungus)
Various fungi were isolated during the course of a survey in a cold-store of apples in the Netherlands. One of these fungi belongs to the genus Penicillium and produces cleistothecia at 9 and 15 °C. A detailed study using a combination of phenotypic characters, sequences and extrolite patterns showed that these isolates belong to a new species within the series Roqueforti. The formation of cleistothecia at low temperatures and the inability to produce roquefortine C, together with a unique phylogenetic placement, make these isolates a novel entity in the Roqueforti series. The name Penicillium psychrosexualis sp. nov. (CBS 128137T) is proposed here for these isolates.